Prognostic Significance of Modified Advanced Lung Cancer Inflammation Index in Patients With Renal Cell Carcinoma Undergoing Laparoscopic Nephrectomy: A Multi-Institutional, Propensity Score Matching Cohort Study - Mao, Weipu; Wang, Keyi; Wu, Yuan; Ni, Jinliang; Zhang, Houliang; Wang, Yidi; Wu, Zonglin; Liu, Ruiji; Geng, Jiang; Chen, Shuqiu; Chen, Ming (Frontiers in Nutrition, 2022)
Background: We conducted a multi-institutional clinical study to assess the prognostic value of the advanced lung cancer inflammatory index (ALI) and modified ALI (mALI) in patients with renal cell carcinoma (RCC). Methods: We collected 440 patients who underwent laparoscopic nephrectomy at three centers from 2014 to 2019. ALI was defined as body mass index (BMI) × serum albumin (ALB)/neutrophil-to-lymphocyte ratio (NLR) and mALI as L3 muscle index × ALB/NLR. Kaplan-Meier curves, receiver operating characteristic (ROC) curves and Cox survival analysis were used to assess the effect of ALI and mALI on overall survival (OS). In addition, we performed 1:1 propensity score matching (PSM) for the high mALI and low mALI groups to further explore the impact of mALI on survival in RCC patients. Results: The optimal cut-off values for ALI and mALI were 40.6 and 83.0, respectively. Based on the cut-off values, we divided the patients into high ALI and low ALI groups, and high mALI and low mALI groups. ALI and mALI were significantly associated with the AJCC stage, Fuhrman grade, T stage, and M stage. Low ALI (p=0.002) or low mALI (p<0.001) was associated with poorer prognosis. ROC curves showed that mALI was a better predictor of OS than ALI. Multivariate Cox regression analysis showed that low mALI (aHR=2.22; 95% CI 1.19-4.13, p=0.012) was an independent risk factor for OS in RCC patients who underwent nephrectomy, while ALI (aHR=1.40; 95% CI 0.73-2.66, p=0.309) was not significantly associated. Furthermore, after PSM analysis, we found that mALI remained an independent risk factor for OS (aHR=2.88; 95% CI 1.33-6.26, p=0.007) in patients with RCC. Conclusions: For RCC patients undergoing laparoscopic nephrectomy, low ALI and low mALI were associated with poor prognosis, and preoperative mALI can be used as a potential independent prognostic indicator for RCC patients.